2021
DOI: 10.3390/microorganisms9010151
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidial Infection Suppresses Intestinal Epithelial Cell MAPK Signaling Impairing Host Anti-Parasitic Defense

Abstract: Cryptosporidium is a genus of protozoan parasites that infect the gastrointestinal epithelium of a variety of vertebrate hosts. Intestinal epithelial cells are the first line of defense and play a critical role in orchestrating host immunity against Cryptosporidium infection. To counteract host defense response, Cryptosporidium has developed strategies of immune evasion to promote parasitic replication and survival within epithelial cells, but the underlying mechanisms are largely unclear. Using various models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…Alternatively, ALK and SCG2 genes were also identified as being associated with the mitogen-activated protein kinase (MAPK) signaling pathway, where both genes are involved in the positive regulation of said cascade (GO:0043410 and GO:0000165, respectively). It has been reported that MAPK signaling is suppressed in host intestinal epithelial cells in an infection caused by Cryptosporidium , which is a protozoan parasite that infects intestinal epithelial cells similar to the Eimeria species [ 63 ]. Along with apoptotic and MAPK pathways, SCG2 has been determined to play a very active role in the formation of innate immune and adaptive immune responses in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, ALK and SCG2 genes were also identified as being associated with the mitogen-activated protein kinase (MAPK) signaling pathway, where both genes are involved in the positive regulation of said cascade (GO:0043410 and GO:0000165, respectively). It has been reported that MAPK signaling is suppressed in host intestinal epithelial cells in an infection caused by Cryptosporidium , which is a protozoan parasite that infects intestinal epithelial cells similar to the Eimeria species [ 63 ]. Along with apoptotic and MAPK pathways, SCG2 has been determined to play a very active role in the formation of innate immune and adaptive immune responses in the body.…”
Section: Discussionmentioning
confidence: 99%
“…However, a signi cant downregulation of p38/Mapk, MAP kinase-activated protein kinase 2 (Mk2), and Mk3 genes was found. This suppression of MAPK signalling activity in C. parvum-infected intestinal epithelial cells was postulated as a strategy to evade host immune response [50].…”
Section: 23mentioning
confidence: 99%
“…Moreover, a significant downregulation of p38/MAPK, MAP kinase-activated protein kinase 2 (Mk2), and Mk3 genes was found in an in vitro model of cryptosporidiosis ( He et al, 2021 ). Suppression of MAPK signaling was linked with an impaired intestinal epithelial defense against C. parvum infection ( He et al, 2021 ) ( He et al, 2021 ). Interestingly, p38/MAPK has described as a tumor suppressor ( Bulavin and Fornace, 2004 ).…”
Section: Modulation Of the Immune Response And Apoptosis Pathwaysmentioning
confidence: 99%